Studies on Transformation and Interference of the Laser Radiation in Composite Crystal Optical Systems - Abilhan Umbetovich Umbetov; Makhabbat Zhaksylykovna Umbetova; Gabit Mukhitovich Abildayev; Saule Svyazkhanovna Baizakova; Samal Arynovna Zhamalova; Arailym Boranbayevna Konussova; Kalamkul Kapenovna Dosmagulova (New Approaches in Engineering Research Vol. 11, 2021)
Crystal optical systems are now being used more frequently in scientific and technical progress. Controlling the amplitude, frequency, phase, and polarisation of laser radiation, as well as scanning an optical beam in space, can be accomplished with their assistance. Furthermore, crystal optical systems are used for spatial encoding and the creation of controlled spatial filters in polarisation interferometers, allowing high-precision investigation of the quality of optical part processing, geometric parameters of laser beams, and the degree of coherence of laser radiation. When laser radiation is directed at the output of crystal optical systems, interference patterns arise, which are used in laser measurement devices for a variety of purposes. Circuit schemes and laser devices should be modified on a regular basis to improve their capacity, accuracy, sensitivity, reliability, and service life. New ideas in crystal optics and laser technology have made it possible to find a solution to these challenges.